Variational Free Energy and Economics Optimizing With Biases and Bounded Rationality - Henriksen, Morten (Frontiers in Psychology, 2020)
The purpose of this paper is to offer a new framework for understanding action, optimization and choice when applied to economic theory more generally. By drawing upon the concept known as the variational free energy principle, the paper will explore how this principle can be used to temper rational choice theory by re-formulating how agents optimize. The approach will result in agent behaviour that encompasses a wide range of so called cognitive biases, as seen in the scientific literature of behavioural economics, but instead of using these biases as further indications of market inefficiencies or market failures, the paper will likewise attempt to show the limits to which these biases can inform or critique standard economic theory. The paper therefore offers up a “middle of the road” approach, in which the neoclassical agent is not quite as “rational” as rational choice theory assumes, but at the same time, not quite as irrational as behavioural economics would often have us believe.